2015
DOI: 10.3233/rnn-140475
|View full text |Cite
|
Sign up to set email alerts
|

Do post-stroke patients benefit from robotic verticalization? A pilot-study focusing on a novel neurophysiological approach

Abstract: Background: Tilt-table equipped with the dynamic foot-support (ERIGO) and the functional electric stimulation could be a safe and suitable device for stabilization of vital signs, increasing patient’s motivation for further recovery, decreasing the duration of hospitalization, and accelerating the adaptation to vertical posture in bedridden patients with brain-injury. Moreover, it is conceivable that verticalization may improve cognitive functions, and induce plastic changes at sensory motor and vestibular sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 54 publications
(55 reference statements)
1
43
0
2
Order By: Relevance
“…Tilt tables are used to verticalize patients safely. Tilt tables that integrate leg movements and/or functional electrical stimulation and hence induce the muscle pump will help to stabilize the cardiovascular system [10], reduce the number of syncopal episodes, and hence decrease therapy interruptions and increase therapy time [11]. Such tilt tables can safely be used even in an intensive care setting [12].…”
Section: Early Therapy Onsetmentioning
confidence: 99%
“…Tilt tables are used to verticalize patients safely. Tilt tables that integrate leg movements and/or functional electrical stimulation and hence induce the muscle pump will help to stabilize the cardiovascular system [10], reduce the number of syncopal episodes, and hence decrease therapy interruptions and increase therapy time [11]. Such tilt tables can safely be used even in an intensive care setting [12].…”
Section: Early Therapy Onsetmentioning
confidence: 99%
“…The improvement could be related to the fact that robotic tilttable rehabilitation may offer standardized, intensive and repetitive exercises, proper body weight support, with an appropriate sensory feedback amount and a controlled progressive verticalization. It was also found in another study that ERIGO training could be a valuable tool for the adaptation to the vertical position with a better global function improvement, as also suggested by the sensory-motor and vestibular system plasticity induction in post-stroke patients [14].…”
Section: Discussionmentioning
confidence: 78%
“…One study suggested that robotic verticalization maximizes the potential for longitudinal weight-bearing through the lower extremities in a position of hipextension/knee-extension/ankle-dorsiflexion, which is difficultly obtained in the physiotherapy verticalization setting. Moreover, robotic verticalization allows strengthening exercises using body weight shifting from one leg to the other, which is not easily carried out by severe post-stroke patients [14]. Some studies found that greater cerebral blood flow modulation during robotic verticalization in comparison to physiotherapy verticalization could further support plastic changes within sensory-motor areas and vestibular system, with the consequent motor and cognitive function amelioration [32,33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first approach relies on the use of an external device (assistant robot or special equipment) which takes up the role of a human assistant [1][2][3]20]. The second approach exploits exoskeleton technology that is currently demonstrating significant progress [14][15][16].…”
Section: Introductionmentioning
confidence: 99%